Aptamer-Driven Toxin Gene Delivery in U87 Model Glioblastoma Cells - di Leandro, Luana; Giansanti, Francesco; Mei, Sabrina; Ponziani, Sara; Colasante, Martina; Ardini, Matteo; Angelucci, Francesco; Pitari, Giuseppina; d’Angelo, Michele; Cimini, Annamaria; Fabbrini, Maria Serena; Ippoliti, Rodolfo (Frontiers in Pharmacology, 2021)
A novel suicide gene therapy approach was tested in U87 MG glioblastoma multiforme cells. A 26nt G-rich double-stranded DNA aptamer (AS1411) was integrated into a vector at the 5’ of a mammalian codon-optimized saporin gene, under CMV promoter. With this plasmid termed “APTSAP”, the gene encoding ribosome-inactivating protein saporin is driven intracellularly by the glioma-specific aptamer that binds to cell surface-exposed nucleolin and efficiently kill target cells, more effectively as a polyethyleneimine (PEI)-polyplex. Cells that do not expose nucleolin at the cell surface such as 3T3 cells, used as a control, remain unaffected. Suicide gene therapy was not observed when the inactive saporin mutant SAPKQ DNA was used in the (PEI)-polyplex, indicating saporin catalytic activity mediates the cytotoxic effect.